Collective hold-up - Matiás Iaryczower; Santiago Oliveros (Theoretical Economics, 2023)
We consider dynamic processes of coalition formation in which a principal bargains sequentially with a group of agents. This problem is at the core of a variety of applications in economics, including lobbying, exclusive deals, and acquisition of complementary patents. In this context, we study how the allocation of bargaining power between principal and agents affects efficiency and welfare. We show that when the principal's willingness to pay is large relative to agents' payoffs for completion, efficiency requires concentrating bargaining power in the principal. Strengthening the bargaining position of the agents increases inefficient delay and reduces agents' welfare. This occurs in spite of the lack of informational asymmetries or discriminatory offers. When this collective action problem is severe enough, agents are better off when bargaining power is concentrated in the principal.
Keywords: C72; C78; D71; D72; 330; Bargaining; contracting externalities; delay; political economy; vote buying